FAILURE ANALYSIS OF BOOM SEAT METAL STRUCTURES - Vitaliy Fedorovich Lukianov; Semen Semenovich Assaulenko (Advanced Engineering Research, 2014)
The causes of the destruction of the crane Gottwald НМК 170 EG (63 t) which happened in 2011 on the territory of “Novorossiysk Commercial Sea Port” are analyzed. The structural and engineering recommendations on the platform bearing capacity restoration are developed. These proposals are based on the failure analysis of the weld joints of the prow rotating platform, and on the 3D numerical simulation of its stress state. It is shown that an abrupt change in the welded assembly compliance in the area of the stiffening ribs supporting the platform bedplate causes a local increase in stress and predetermines the fatigue-crack nucleation. The results of the crack nucleation regions simulation are in good agreement with the crane diagnostic results. It is shown that the stress localization in the welded node joints with non-uniform compliance of the connected components is a common pattern. It must be taken into account in both the designing and the development of the repair technique. A specific case suggests extra pads to provide a smooth change in the welded assembly compliance in the area of the platform stiffening rib under the weld assembly repair.